2007
DOI: 10.1021/es062962x
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Effects of Catalytic Diesel Particulate Filters:  Copper-Induced Formation of PCDD/Fs

Abstract: Potential risks of a secondary formation of polychlorinated dibenzodioxins/furans (PCDD/Fs) were assessed for two cordierite-based, wall-through diesel particulate filters (DPFs) for which soot combustion was either catalyzed with an iron- or a copper-based fuel additive. A heavy duty diesel engine was used as test platform, applying the eight-stage ISO 8178/4 C1 cycle. DPF applications neither affected the engine performance, nor did they increase NO, NO2, CO, and CO2 emissions. The latter is a metric for fue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(81 citation statements)
references
References 27 publications
3
78
0
Order By: Relevance
“…Many factors, such as fuels, engine types, test modes, after treatment technologies that can affect PCDD/F emissions from vehicles have been discussed in previous study and review articles (Heeb et al, 2007;Chuang et al, 2010Chuang et al, , 2011Chang et al, 2014b;Rey et al, 2014;Mwangi et al, 2015). Here we aim to focus on how to conduct vehicular exhaust samplings to obtain better quality data to estimate PCDD/F emission factors from mobile sources.…”
Section: Pcdd/f Emissions From Mobile Sourcesmentioning
confidence: 99%
“…Many factors, such as fuels, engine types, test modes, after treatment technologies that can affect PCDD/F emissions from vehicles have been discussed in previous study and review articles (Heeb et al, 2007;Chuang et al, 2010Chuang et al, , 2011Chang et al, 2014b;Rey et al, 2014;Mwangi et al, 2015). Here we aim to focus on how to conduct vehicular exhaust samplings to obtain better quality data to estimate PCDD/F emission factors from mobile sources.…”
Section: Pcdd/f Emissions From Mobile Sourcesmentioning
confidence: 99%
“…Heeb et al (2007) assessed 2 kinds of DPFs installed on a heavy-duty diesel engine. Their results show THC emissions decreased by about 40% when deploying DPFs.…”
Section: Introductionmentioning
confidence: 99%
“…Formation of PCDD/Fs in vehicle engines requires both incomplete combustion process and presence of chlorine (UNEP, 2003), which may arise from Cl À in airborne particulates (Deng et al, 2011). Furthermore Cu, a catalyst for PCDD/F formation (Heeb et al, 2007), was also found in residue formed in the fuel supply system of LPG-vehicles for the usage of copper pipeline (Gao et al, 2007). Our data suggested that PCDD/ Fs emitted from LPG-buses might be lower than HDDVs, but higher than gasoline-powered cars.…”
Section: Calculationmentioning
confidence: 99%
“…Summarizing published data, PCDD/F emission factors are typically in the range of 0.36-9500 pg I-TEQ km À1 (7.0-27440 pg I-TEQ L À1 ) ) and are correlated with engine type, load and age, fuel type and quality, driving mode, etc. Ryan, 1997, 2002;Miyabara et al, 1999;Kim et al, 2003;Heeb et al, 2007). Low load rates and idle conditions reportedly greatly increase dioxin emission from diesel-vehicles (Kim et al, 2003;Chang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%